Effect of cultural tightness-looseness on money laundering: a cross-country study. Issue 2 (14th June 2021) - Mejri, Mariem; Othman, Hakim Ben; Al-Shattarat, Basiem; Baatour, Kais
Abstract : Purpose: The purpose of this interdisciplinary cross-country study is to investigate the influence of cultural tightness-looseness on money laundering. Design/methodology/approach: The authors rely on tightness-looseness theory as the basis for their predictions. The authors use the Basel Anti Money Laundering Index to operationalize financial crimes. They use dynamic panel data regressions spanning from 2012 to 2018 across 66 countries. Findings: The authors find a positive and significant effect of national culture on money laundering financial crime. This suggests that financial crimes increase in countries with higher levels of cultural looseness orientation. Moreover, the authors show that the absence of violence, control of corruption, political stability and voice and accountability has a significant and negative influence on money laundering financial crime. Practical implications: Formal institutional factors are not the only factors that can help curb financial crimes, but policy regulators should also consider the degree of cultural tightness-looseness. Originality/value: To the best of authors' knowledge, this is the first research ever to examine the effects of cultural tightness-looseness on the level of financial crimes.